Wellbeing of Mice Euthanized with Carbon Dioxide in Their Home Cage as Compared with an Induction Chamber - Hickman, Debra L (J Am Assoc Lab Anim Sci, 2021)
The AVMA Guidelines on Euthanasia state that, to decrease potential distress of animals, the home cage should be used for the euthanasia of mice. The current study evaluated this recommendation by comparing behavioral and physiologic changes in ICR and SJL mice that were euthanized by using a 30% volume per minute displacement rate of 100% CO(2) in either their home cage or an induction chamber. Blood samples were collected to assess blood glucose, serum corticosterone, and serum noradrenaline as markers of physiologic wellbeing. Behavioral assessment was performed (with emphasis on behaviors including rearing, jumping, sniffing at the gas inlet, and grooming) from the introduction of gas to the estimated time to loss of consciousness (i.e., the time period when the animal would be expected to experience pain or distress). Despite significant differences between mouse strains, no significant differences were detected in the physiologic or behavioral parameters assessed when comparing the home cage with the induction chamber. This finding suggests that— from the perspective of a mouse—either the home cage or an induction chamber can be used for induction of anesthesia with CO(2) during the euthanasia procedure.